Pre-service Science Teachers’ Nature of Science Understandings’ Influence on Their Socioscientific Argumentation Quality - Kutluca, Ali Yiğit; Aydın, Abdullah (Elementary Education Online, 2018)
The purpose of this study is to investigate pre-service science teachers’ (PSTs’) nature of science (NOS) understandings’ influence on their socioscientific argumentation quality. This study was conducted with 12 participants whom were chosen with maximum variation sampling method among 27 PSTs. The class of the participants was chosen by basic random sampling method. This study, which contains both qualitative and quantitative processes, is an explanatory mixed method in which quantitative data are used in more detail than qualitative data. For this study, which lasted 11 weeks in total, three groups with four participants in each were formed. Presentations, whole-class discussions and small group discussions were made for participants to learn fundamental knowledge about the NOS and socioscientific argumentation; and to have them basic argumentation formation skills. Qualitative and quantitative data analyses indicate that understanding (low, medium, high) of the NOS impacts socioscientific argumentation quality. Our results also indicate that superior understanding of the NOS also predicts socioscientific argumentation quality.
Keywords: 4. Education; 16. Peace & justice